Pengaruh Praktek Kerja Industri (Prakerin), Informasi Dunia Kerja Dan Motivasi Memasuki Dunia Kerja Terhadap Kesiapan Kerja Siswa SMK - Sari, Yesi Puspita; Mariyanti, Eka (CV. ITTC INDONESIA, 2024)
This study aims to analyze the effect of Industrial Work Practice (PRAKERIN), information on the world of work, and motivation to enter the world of work on the work readiness of XII grade students at the Vocational High School for Agricultural Development (SMK PP) Negeri Padang. By using a sample of 105 students, the sampling technique was carried out using Raosoft Sample Size Calculator Software. The results of data analysis show that the variable that has the most influence on the work readiness of vocational students is Industrial Work Practice (PRAKERIN), with a beta value of 0.477. This study highlights the importance of practical experience in shaping vocational students' work readiness, and emphasizes the need for increased information and motivation related to the world of work. The implication of this finding is the need to improve and develop the PRAKERIN program at SMK PP Negeri Padang, as well as the important role of information and motivation in preparing students to enter the world of work. This research contributes to the understanding of the factors that influence vocational students' work readiness, so that it can be the basis for developing more effective educational strategies and policies in the future.